Pendampingan Kader Keluarga Berencana Dalam Pengisian Aplikasi Rumah Dataku Sebagai Upaya Mewujudkan Kampung Kb Berkualitas Di Desa Pasir Panjang Kabupaten Pandeglang - Rahmawati Allyreza; Rezki Ardiyanto; Enifia Adhitia Catherine (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Pasir Panjang Village is one of the developing village categories which has three Family Planning villages (Kampung KB) out of the nine existing villages. One of the instruments in Kampung KB is Rumah DataKu. Preliminary observations found that data availability, the ability of family planning cadres, and network access were obstacles in filling out the Rumah DataKu application. There fore this activity aims to assist family planning cadres in filling in Rumah DataKu application data in Pasir Panjang Village. The method used is outreach and assistance to family planning cadres and the community participating in the activity. The results of the activity found that the limitations of population data were the main problem, the ability of family planning cadres to understand the Rumah DataKu application was still lacking and there was no budget allocation from the village to collect population data for the Rumah Dataku application.